Analisis Pelaksanaan Program Bantuan Stimulan Perumahan Swadaya (BSPS) Dinas Perumahan Rakyat dan Kawasan Permukiman Sesuai Prinsip Keadilan dan Ketepatan untuk Penerima Program Rumah Layak Huni - Seri Mughni Sulubara; Amrizal Amrizal; Ashari Efendi; Budiman Budiman; Evi Lestaria; Zainal Abidin; Ranti Maulya (Pusat Riset dan Inovasi Nasional, 2024)
The implementation of Self-Help Housing Stimulant Assistance requires community involvement to achieve its goal of providing livable houses for the implementation of the Self-Help Housing Assistance Program (BSPS) for Low-Income Communities (MBR) in Negeri Antara Village. As an implementation of the legal basis that has been mentioned, the government through the Ministry of Public Works and Public Housing (PUPR) is forwarded to the Directorate General of Housing together with the Directorate of Self-Help Houses to make it easier for the community, especially low-income people, to realize the improvement of uninhabitable houses both from facilities, infrastructure, and public utilities by designing a policy namely Self-Help Housing Stimulant Assistance (BSPS). The problem in this research is that there are still inaccurate beneficiaries and there are still beneficiaries who have stopped in carrying out house construction activities due to lack of self-help funds. The purpose of this research is to find out data related to the principles of accuracy and justice in terms of the Evaluation of the Self-Help Housing Stimulant Assistance Program (BSPS) in Negeri Antara Village, Pintu Rime Gayo District, Bener Meriah Regency, Aceh Province, which is known that the BSPS program is a program of the Ministry of Public Housing of the Republic of Indonesia in order to support poverty reduction and efforts to prosper the poor so that they can have a decent home in a healthy environment.